Interaction between bioaccumulation and the efficiency of intermittent sand filters in wastewater treatment. (10th February 2022) - Wu, Zhongyu; Dougherty, Mark; Chen, Zhongbing; Zhou, Yun; Zuo, Xingtao; He, Jiajie
Abstract: Decentralized onsite wastewater treatment systems (OWTS) play an important role in alleviating the global carbon emissions pressure and meeting the United Nations Sustainable Development Goal for 2030. As a type of OWTS, intermittent sand filters (ISF) have a wide application in rural areas, but bioaccumulation caused bioclogging threatens its viability as a rural wastewater treatment technology. Proper understanding of the relationship between bioclogging and wastewater treatment is fundamental to the environmental sustainability of ISF. In this study, the interplay of ISF bioclogging and wastewater treatment efficiency is described by a mechanistic deterministic model to explore the role of bioclogging in ISF performance. The model incorporates variably saturated flows, reactive pollutant transport, bacterial growth, bioclogging caused soil permeability change, and reactive gas-phase oxygen transport and provides several insights regarding ISF operations. It is demonstrated that bioclogging as a result of wastewater treatment is necessary in maintaining adequate wastewater treatment efficiency. Bioclogging zone is the most active wastewater treatment region and the coupling between stimulated oxygen utilization rate and triggered oxygen replenishment rate is decisive in bioclogging development speed and effluent N profile. Overall, this study challenges the traditional negative viewpoint toward bioclogging, and the positive and negative aspects of bioclogging in ISF can be managed to promote the environmental sustainability of ISF. Graphical abstract: Image 1 Highlights: Multiphase and multicomponent ISF processes are described numerically. The presence of bioclogging is necessary to maintain wastewater treatment efficiency. Bioclogging discourages both advection and diffusion oxygen replenishment in ISF. An optimum ISF operation exists to balance the pros and cons of bioclogging.